ANALISA SISTEM KENDALI KECEPATAN MOTOR BLDC PADA MOBIL AUTONOMOUS MENGGUNAKAN PWM (PULSE WIDTH MODULATION) BERBASIS ARDUINO - Amran, Fajar; Amperawan; Annisah, Masayu (JURNAL TELISKA, 2023)
Bldc motor is an alternative component for autonomous electric car because it has several advantages over conventional DC motors which still use brushes and commutators, while bldc motors do not use brushes and commutators but use electronic circuits to control the bldc motor with high efficiency, high operating life, high maintenance. low and low noise. By using a universal mosfet driver that has a hall effect sensor, hall effect can help calculate the pwm of a bldc motor controlled by arduino. The arduino controlling the universal mosfet driver will calculate using the pwm system of the bldc motor. This system will help the autonomous electric car transportation industry in controlling speed.